Application of Co-Production in Waste Management Through Waste Banks Program in Batu City - Sulung Satriyo Irkham; Muhammad Kamil; Saiman H (Journal of Local Government Issues (LOGOS), 2019)
The problem of waste in Batu City can threaten tourism sector in this city. The Waste Management System Program is held by the Environment Agency (DLH) Batu City seems to be unable to access waste problems in the upstream sector, particularly  household waste from residential settlements. This lack capacity of the program followed up by DLH by organizing a waste bank program through the establishment of the Community Waste Bank (KBS) Kartini Sejati which coordinated around 60 waste banks in Batu City to be involved in waste management.This study aims to explain the involvement of KBS Kartini Sejati in waste management in co-production and the obstacles faced by it. The concept of co-production refer to an alternative concept in the implementation of public services where implementation focuses on the dominant role of the community, while the government or other parties such as the private sector are only facilitators. This research  use qualitative method by utilizing data from observations, interviews and documentation. The results of this study indicate that KBS Kartini Sejati in several of its activities which include training in waste management, waste management, and "Sapu Bersih Sanpah Nyemplung Kali" (Saberpungli) have applied the principles of co-production. It is due to those activities have implemented six co-production principles, namely the development of community capacity, mutually beneficial relationships between actors, network development, the government as a facilitator and catalyst, and the community as an important asset in implementing services. However, in its implementation, the waste bank program still has several obstacles such as the limitations of the budgetary resources, the decreasing level of public awareness to be active in waste banks, and the lack of innovation in waste managementKeywords: Co-production; waste management, waste bank